The Impact of Privatization on Economic Growth: The Case of Uzbekistan - Shukurov, Sobir; Maitah, Mansoor; Smutka, LuboÅ¡ (International Journal of Economics and Financial Issues, 2016)
This paper clarifies the macroeconomic gains from privatization during the transition period in Uzbekistan. The choice of this country is due to its stable macroeconomics performance beginning from 1996 onwards, and author's related work experience at The State Committee of the Republic of Uzbekistan for Privatization. Based on the macroeconomic empirical literature on growth, we supplement the standard model of GDP growth with other transition-specific variables to investigate the impact of privatization on economic growth. In so doing, we found that economic growth was significantly influenced by investment (more importantly investment to the education), and employment growth. Several other institutional components specific to the transition process, particularly the private sector and capital market development, and small-scale privatization were also found to be significant determinants of economic development in Uzbekistan.